Advanced Health Control Consultation Application at Clinic B White C Based on Android - Akbar Iskandar; Andryanto Aman; Dayun Miyanti; Muhammad Akram Hamzah; Tatik Maslihatin (Ceddi Journal of Information System and Technology (JST), 2022)
Health information is a very important part of everyday life, where health information is obtained through direct consultation with doctors. However, in the midst of the Covid-19 pandemic that hit, we are required to continue to follow the health protocols recommended by the government by keeping a distance from each other or social distancing. Consultations are carried out face-to-face with doctors and conventional consultation methods prolong the meeting time between doctors and patients. Based on interviews conducted with several patients in several clinics, patients obtain health information by visiting the clinic and consulting directly with doctors. The purpose of this research is to build an Android-based Health Control Consultation application with an Information Technology approach, which is a form of service application. This application was built so that patients can find out health information through questions and answers via e-consul. Patients enter questions about health problems or health problems in text form, then the e-consul will respond to patient questions. So that it can facilitate someone in health consultations and obtain information on health problems and provide first aid information when a symptom or disease occurs. The E-consul application is also equipped with articles so that doctors can also share information from their knowledge with patients. This application is built by utilizing mobile-based application technology.